Konstruksi Santri atas Kepemimpinan Multikultural Pondok Pesantren Ngalah Pasuruan - Shofi, Ibnus (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2024)
Indonesia is a highly multicultural nation, with diverse ethnic, religious, and cultural groups. Managing this richness to build collaboration and prevent destructive conflict is a significant challenge, requiring strong tolerance and mutual respect. Education, including within pondok pesantren, is crucial role for fostering understanding and cultivating multicultural values as prerequsite for sinergic collaboration. This study investigates Pondok Pesantren Ngalah, founded by Kiai Sholeh, known for his tolerance. The research specifically examines how santri construct the meaning of Kiai Sholeh's multicultural leadership, essential for evaluating the success of instilling these values. Using a qualitative phenomenological approach, data was gathered via interviews, observation, and documentation. Findings indicate santri perceive Kiai Sholeh's leadership as an ideal model, grounded in his exemplary behaviour, inclusive theological interpretations, moderate fiqh, focus on positive human potential, and multicultural activities. This integrated construction underpins the cultivation of multicultural values, recommending emulation for other institutions